Trauma of Migration and Environment: An Ecocritical Analysis of Exit West - Tahir, Alina; Rabbani, Munazzah (Annals of Human and Social Sciences, 2024)
The present study probes the effects of toxic discourse and trauma through which both humans and environment suffer in the novel Exit West (2017). The main objective of this research is to identify the toxicity and devastation of refugees and environment through trauma of migration. The study is qualitative in nature and Buell’s Toxic Discourse (1998) and Caruth’s Trauma Theory (1996) have been applied as a framework for the study. Analysis has been done by the use of textual method. Hence, the findings revealed that migration is a terrible event of human history which effects people both mentally and physically. Migration is a global issue and Exit West (2017) revealed that how time and climate act as the working force behind this terrifying journey.